Improving of computed tomography images for effective diagnosis of gunshot wounds - E.M. Khoroshun; K.S. Smelyakov; A.S. Chupryna; V.V. Makarov; V.V. Nehoduiko; Ye.V. Vakulik (Медицина неотложных состояний)
Background. The purpose of the work is to develop gradation correction models, methods, and test software that can be quickly applied to improve X-ray and computed tomography (CT) images in automatic mode under conditions of time constraints, as well as significant distortion of the dynamic range of density due to the presence of high-density metal objects, significant manifestation of the gloss effect. Materials and methods. To achieve this, experiments were planned and conducted to obtain CT scans of the organs of interest with metal fragments of the given types placed in them. All the fragments were photographed and measured by a group of independent experts for the possibility of further comparative analysis by classical and computer methods, evaluation of the quality of improved images by numerical and visual methods. Results. Based on experimental data, a new unified model, method and test software for gradation correction of X-ray and CT images have been developed, the use of which allows you to significantly improve the quality of images (up to 5 times in the sense of increasing contrast) in real time (most often, the processing time of one image does not exceed 1 second). The proposed model, method and software are unified in terms of file formats, automatically adjust to the density scale and process data. Conclusions. The developed model, method and software make it possible to achieve the goal of the work — to provide prompt improvement of X-ray and CT images in automatic mode in conditions of lack of time, as well as significant distortion of the dynamic range of density, significant manifestation of the gloss effect. This makes it possible to quickly and qualitatively diagnose gunshot wounds. High efficiency is confirmed by the results of numerous experiments and implementation. At the same time, thanks to a one-time adjustment by a highly qualified expert, the proposed software can be applied with high efficiency in a mass order using preset parameters.